Physicochemical characterization of Chiapas ethnic cheeses - Rosado-Zarrabal, Thelma Lucía (Universidad Autónoma de Tamaulipas, 2013)
Nowadays, cream cheeses made in the Costa, Selva and Norte Regions of the State of Chiapas are the best selling cheeses. These cheeses are not produced on a large scale and they are heterogeneous. However, they are well accepted among consumers for their sensory characteristics. The purpose of this project was to characterize the ethnic cheeses from Chiapas by physicochemical analysis to verify if the characteristics were within the limits of the NMX-F-092-1970 and NOM-243- SSA1-2010 norms. Samples of cream cheese produced in different regions of Chiapas were compiled and analyzed to characterize pH, content moisture, total solids, lipid, protein and ashes content. Then, they were compared with the norms. Results indicated that, except pH, the cream cheese from Costa, Selva and Norte Regions in the State of Chiapas complied with the Mexican Officials Norms, and Costa Region cream cheese was high in ash (4.49 %). However, in relation to fat, solids, moisture and proteins contents, they were equal in the three regions and are therefore cheeses with desirable nutrient value.